Identification of a SSR marker (TOM-144) linked to Fusarium wilt resistance in Solanum lycopersicum - Parmar, Pritesh; Sudhir, Ankit; Preethi, R.; Dave, Bhaumik; Panchal, Ketankumar; Subramanian, Ramalingam B.; Patel, Arvind; Kathiria, K. B. (Scientific Research Publishing, 2013)
With the discovery of molecular markers and marker assisted selection technology, the research has entered into a new era and has made it possible to develop new and more informative PCR-based markers, including SSR, and to further facilitate the use of markers in tomato breeding. The present study is a step to introduce a new SSR marker (TOM-144) which was deduced after evaluation of eight microsatellite loci amongst the twenty-one different tomato cultivars. The marker selected was inherited and segregated in mendelian fashion as demonstrated in successive generation of a cross between parent cvs. H-24 x GT-2.
Keywords: Fusarium Wilt; Molecular Marker; Tomato